Evaluation of Screening Program for Development Dislocation of Hip in Primary Health Care Centers in Karbala City - Raheem, Dr. Buraq Mohammed; Alasad, Dr. Buriar Mohammed Ali; Obaid, Dr. Salam Sahib; AlKhazraji , Dr.Hussain Ali Hakeem (Open Journal of Physicians and Surgeons, 2024)
Background: Developmental Dysplasia of the Hip (DDH) is a significant cause of disability in children and young adult. Early detection and early treatment prevent such disabilities and offer a less expensive and simpler mod of treatment. Objectives: To determine the incidence of DDH and to evaluate the screening programs for detecting DDH in PHCs in Karbala city Subjects and Methods: A cross-sectional study was carried out from February 2018 till February 2019 (12 months) in five primary health care centers in Karbala city which adopted the universal and selective ultrasound screening. Only 823 infants’ records were complete and included in our study. The results of Ultrasound examination were classified according to Graf’s method. Results:This study includes 823 infants’ records, majority of them (94.2%) delivered in hospitals. A significant gender difference between the universal and selective ultrasound screening (p=0.0001). Proportion of infants delivered by Cesarean section was significantly higher in universal compared to selective screening (p=0.003). There were only 49 infants showed positive clinical examinations. Only 14 infants had DDH, three cases diagnosed through universal while 11 cases diagnosed with the selective screening. In the present study, Conclusions: The incidence of DDH is significantly higher than other studies. It was more frequent in Females. Bilateral hip anomalies are in about half of DDH cases and the left side is the most common.